Analisis Simpeg, Budaya Kerja Dan Disiplin Kerja Terhadap Kinerja Dengan Model Mediasi - Fitriyati, Atika Ayu Fitriyati; Suyanto, Suyanto; amir, Ja'far Amir (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Personnel Management Information System (PMIS), is an important factor in the Deputy for Industry and Investment of the Ministry of Tourism and Creative Economy, in improving employee performance. The SEM-PLS approach was carried out to examine the pattern of PMIS relationships, classification, work culture and employee performance. The questionnaire was distributed online to 110 employees, who then processed the data with SmartPLS4 software. It was revealed that discipline and work culture became mediating variables that fully influenced PMIS on employee performance. In its ever-evolving nature, PMIS is always relevant for further research regarding the emergence of new work patterns such as Work from home (Work form Home).